Cervical Cancer at Mbarara Regional Referral Hospital: Magnitude, Trends, Stages at Presentation, Impact of Acetic Acid Screening and the Need for Radiotherapy Services - Ronald, Mayanja; Andrew, Chakura; Sezalio, Masembe; John, Kasujja; Hillary, Aheisibwe; Kayondo, Musa; Hamson, Kanyesigye; Ssalongo, Wasswa; Mukasa, Peter; Sanchez, Caesar Emilio; Ngonzi, Joseph (Journal of Health, Medicine and Nursing, 2016)
Background: Globally, cervical cancer the fourth most common cause of cancer death accountable for approximately 266,000 deaths of women, with sub-Saharan Africa and East Africa having the highest burden. In Uganda about 2,275 new cervical cancer deaths occur annually. The main objective of the study was to describe the magnitude, trends, clinical stage on presentation and show the importance of cervical cancer prevention and radiotherapy services at Mbarara Regional Referral Hospital. Methods: This was a descriptive cross-sectional study. In the first phase of the study, leading cancers at Mbarara Regional Referral Hospital were determined. In the second phase of the study, the burden of cervical cancer on the gynecological ward was determined. In the third part of the study the trends of cervical cancer over a ten year period was determined. In the fourth phase of the study the effects of acetic acid screening on the trends of cervical cancer was determined. Results: With a proportion of 25.2%, cervical cancer is the single leading cancer in the hospital. Cervical cancer contributes 10.1% of all diseases on the gynecological ward and 73.9% of all gynecological cancers. The frequency of cervical cancer more than doubled between 2006 and 2014) with 60.3% of presenting with late stage. The number of cases of early cervical cancer detected had shown a small but steady increase since 2009. There was a decline in clinic cervical cancer incidence rate from 3.2% in 2009, 0.9% in 2013. Conclusion: Cervical cancer is the leading cancer and also the leading gynecological cancer at Mbarara Regional Referral Hospital. Women with cervical cancer are diagnosed late. Screening increases the rate of early detection. Acetic acid screening is effective in reversing the trends of cervical cancer. Expanding cervical cancer preventive services is capable of reducing the burden of cervical. Recommendations: There is need for expansion of HPV vaccination. There is need for expansion of acetic acid cervical cancer screening in southwestern Uganda. There is need for making radiotherapy services more accessible in developing countries.
Keywords: Cervical Cancer; Magnitude; Trends; Stages; Impact; Acetic Acid; Screening; Radiotherapy